Kepastian Hukum Penyelesaian Sengketa Medis Melalui Mediasi di Luar Pengadilan - Afiful Jauhani, Muhammad; Supianto, Supianto; R. Hariandja, Tioma (WELFARE STATE Jurnal Hukum, 2022)
The provisions of Article 29 of Law Number 36 of 2009 concerning Health states that, in the event that a health worker is suspected of negligence in carrying out his profession, the negligence must be resolved first through mediation. The explanation of the article states that, Mediation is carried out when a dispute arises between health workers providing health services and patients as recipients of health services. Mediation is carried out with the aim of resolving disputes out of court by a mediator agreed by the parties. This type of research is normative juridical. Normative law research uses normative case studies in the form of products of legal behavior, for example reviewing laws. Based on the research, it can be concluded that mediation efforts to resolve media disputes outside the court are more flexible regarding the time and place of implementation. and is considered capable of maintaining the confidentiality of the disputing parties. The peace agreement resulting from mediation of medical disputes outside the court which has been determined by the Court as a deed of peace (acte van dading) has the same power as a court decision which has permanent legal force (incracht van gewijsde), so it has binding and final force (final and binding). ), perfect evidentiary power as well as executorial power.